Fast and smooth control of converter’s DC-link voltage using optimal fractional-order interval type-2 fuzzy controller - Asakereh, Aghil (Engineering Research Express, 2025)
The need to use fully controlled AC/DC converters for DC-based power supply systems has led to structural development and improved performance. Due to existence of various distribution network loads sensitive to noise and fluctuation, PWM-based converters cannot provide accurate and fast performance. In this regard, this paper suggests a novel robust control strategy based on FOIT2FC for this distribution power system to enhance the tracking accuracy and smooth the DC voltage of converter’s DC-link with presence of system uncertainties and disturbances. To strengthen the proposed control strategy, MOMSA has been utilized to optimally tune the FOIT2FC’s parameters. Precise and robust tracking performance of the proposed MOMSA-based FOIT2FC has been thoroughly compared with PSO-based FOIT2FC, PSO-based IT2FC and PSO-based Fuzzy controllers under DC reference variation, resistive load variation, unbalanced three-phase voltage and reproductive operation. The simulation results show that the proposed MOMSA-based FOIT2FC almost gives 1.53% overshoot, 1.25% undershoot and 0.023% fluctuation, while PSO-based FOIT2FC gives 1.95% overshoot, 1.89% undershoot and 0.14% fluctuation, PSO-based IT2FC gives 2.46% overshoot, 2.38% undershoot and 0.19% fluctuation and PSO-based Fuzzy controller gives 2.74% overshoot, 2.95% undershoot and 0.22% fluctuation. To more certify the simulation model, its prototype structure has been provided and tested in laboratory.